Makna Berpacaran Yang Benar Menurut Kidung Agung 8:6 - Lylyan Firdaus; Agus Prayitno M. Th (FILADELFIA: Jurnal Teologi dan Pendidikan Kristen, 2021)
Dating is a familiar thing, but many do not understand the true meaning of dating. This study aims to find out and understand the true meaning of dating, so as to minimize and even stop the problems caused by dating. The research used qualitative and quantitative methods. So using literature, hermeneutics, exposition, interviews, questionnaires, graphs, tables, and pictures. This is done to get more valid and accurate research results. The research was conducted at a high school consisting of 30 people with a sample of 21 students.Based on Kid. 8:6-7, true courtship is having the goal of being united with his beloved in holy marriage. True dating requires seriousness with a sign of approval. True dating is pure like love from God. And the love that exists in dating is unmatched by anything, both wealth and problems. However, not all students in the research area understand this. Not understanding students are influenced by the wrong mindset.